Impact of Coronavirus Disease 2019 Public Health Measures on Detections of Influenza and Respiratory Syncytial Virus in Children During the 2020 Australian Winter. (24th September 2020) - Yeoh, Daniel K; Foley, David A; Minney-Smith, Cara A; Martin, Andrew C; Mace, Ariel O; Sikazwe, Chisha T; Le, Huong; Levy, Avram; Blyth, Christopher C; Moore, Hannah C
Abstract: Public health measures targeting coronavirus disease 2019 have potential to impact transmission of other respiratory viruses. We found 98.0% and 99.4% reductions in respiratory syncytial virus and influenza detections, respectively, in Western Australian children through winter 2020 despite schools reopening. Border closures have likely been important in limiting external introductions.